Overexpression of Notch3 and pS6 Is Associated with Poor Prognosis in Human Ovarian Epithelial Cancer - Zhaoxia Liu; Rongna Yun; Xiaolin Yu; Hui Hu; Genhua Huang; Buzhen Tan; Tingtao Chen (Hindawi Limited, 2016)
Notch3 and pS6 play important roles in tumor angiogenesis. To assess the expression of Notch3 and pS6 in Chinese ovarian epithelial cancer patients, a ten-year follow-up study was performed in ovarian epithelial cancer tissues from 120 specimens of human ovarian epithelial cancer, 30 specimens from benign ovarian tumors, and 30 samples from healthy ovaries by immunohistochemistry. The results indicate that the expression of Notch3 and pS6 was higher in ovarian epithelial cancer than in normal ovary tissues and in benign ovarian tumor tissues (p<0.01). In tumor tissues, Notch3 expression and pS6 expression were negatively associated with age (p>0.05) but positively associated with clinical stage, pathological grading, histologic type, lymph node metastasis, and ascites (p<0.05 or p<0.01). A follow-up survey of 64 patients with ovarian epithelial cancer showed that patients with high Notch3 and pS6 expression had a shorter survival time (p<0.01), in which the clinical stage (p<0.05) and Notch3 expression (p<0.01) played important roles. In conclusion, Notch3 and pS6 are significantly related to ovarian epithelial cancer development and prognosis, and their combination represents a potential biomarker and therapeutic target in ovarian tumor angiogenesis.